2016
DOI: 10.1371/journal.pntd.0004992
|View full text |Cite|
|
Sign up to set email alerts
|

Meta-transcriptome Profiling of the Human-Leishmania braziliensis Cutaneous Lesion

Abstract: Host and parasite gene expression in skin biopsies from Leishmania braziliensis-infected patients were simultaneously analyzed using high throughput RNA-sequencing. Biopsies were taken from 8 patients with early cutaneous leishmaniasis and 17 patients with late cutaneous leishmaniasis. Although parasite DNA was found in all patient lesions at the time of biopsy, the patients could be stratified into two groups: one lacking detectable parasite transcripts (PTNeg) in lesions, and another in which parasite transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
68
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(76 citation statements)
references
References 31 publications
8
68
0
Order By: Relevance
“…In human disease, this has largely focused on cutaneous leishmaniasis 35– 37 . A single study has reported on transcriptional changes in the draining lymph node of Sudanese patients with VL before and after treatment with sodium stibogluconate, identifying a potential role for nuclear factor of activated T cells (NFAT)-regulated immune responses in treatment response 38 .…”
Section: Introductionmentioning
confidence: 99%
“…In human disease, this has largely focused on cutaneous leishmaniasis 35– 37 . A single study has reported on transcriptional changes in the draining lymph node of Sudanese patients with VL before and after treatment with sodium stibogluconate, identifying a potential role for nuclear factor of activated T cells (NFAT)-regulated immune responses in treatment response 38 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, RNA-seq of LCL patient biopsies revealed lesional skin containing detectable L. ( V. ) braziliensis transcripts had a unique transcriptional signature compared with lesional skin that did not contain L. ( V. ) braziliensis transcripts [ 80 ]. Although inflammatory gene transcripts (IFNG and TNF) were increased in these lesions indicative of an active adaptive response, there was a concomitant increase in transcripts encoding inhibitory molecules (IL10, CTLA4, PD1, PDL1, and LAG3).…”
Section: Localized Cutaneous Leishmaniasismentioning
confidence: 99%
“…Although inflammatory gene transcripts (IFNG and TNF) were increased in these lesions indicative of an active adaptive response, there was a concomitant increase in transcripts encoding inhibitory molecules (IL10, CTLA4, PD1, PDL1, and LAG3). Interestingly, parasite transcript-positive skin was also associated with a significant increase in B cell transcripts (CD79A, CD19, and CD20), suggesting B cell infiltration during active infection [ 80 ]. This is supported by another study showing an increase in B cells in L. ( V. ) braziliensis infected patient lymph nodes during the progression from early pre-lesional to lesional phases of diseases [ 81 ].…”
Section: Localized Cutaneous Leishmaniasismentioning
confidence: 99%
“…Another lipid phosphatase (encoded by LbrM. 25.21.80) may contribute to the parasite virulence, as it was shown to be among the 100 most abundantly expressed genes in Leishmania braziliensis skin lesions of humans with cutaneous leishmaniasis [20].…”
Section: Introductionmentioning
confidence: 99%